Financial Digitalization on Operational Efficiency and Corporate Value in the Era of Industry 5.0 - Sri Maria Ulfha (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid advancement of digital technologies has transformed financial operations worldwide, making financial digitalization a critical driver of efficiency, transparency, and value creation in the emerging era of industry 5.0. This study investigates the impact of financial digitalization on operational efficiency and corporate value within the context of industry 5.0. Using a qualitative research methodology, specifically a literature review (library research), the study explores the integration of digital financial technologies such as blockchain, artificial intelligence, and cloud computing into business operations. The results reveal that financial digitalization significantly enhances operational efficiency by automating processes, reducing costs, and enabling real-time decision-making. Additionally, it fosters corporate value creation by improving decision-making, transparency, and customer trust. However, challenges such as high implementation costs, cybersecurity risks, and organizational resistance to change were also identified. The study highlights the role of industry 5.0 in driving human-machine collaboration, where financial digitalization facilitates both operational improvements and long-term business value. The findings provide important insights for businesses, particularly in understanding the critical factors and barriers to adopting digital financial